Evaluation for the real world : the impact of evidence in policy making - Palfrey, Colin (Policy, 2012)
"Evaluation research findings should be a key element of the policy-making process, yet in reality they are often disregarded. This valuable book examines the development of evaluation and its impact on public policy by analysing evaluation frameworks and criteria which are available when evaluating public policies and services. It further examines the nature of evidence and its use and non-use by decision-makers and assesses the work of influential academics in the USA and UK in the context of evaluation and policy making. The book emphasises the 'real world' of decision-makers in the public sector and recognises how political demands and economic pressures can affect the decisions of those who commission evaluation research while providing recommendations for policymakers on adopting a different approach to evaluation. This is essential reading for under-graduate and post-graduate students of policy analysis and public sector management, and those who are involved in the planning and evaluation of public policies and services."--Publisher's website.